Effect of SARS-CoV-2 Infection on Selected Parameters of the Apelinergic System in Repeat Blood Donors - Marta Stanek; Anna Leśków; Dorota Diakowska (Biomedicines)
Background: SARS-CoV-2 enters cells primarily by binding to the angiotensin-converting enzyme 2 (ACE2) receptor, thereby blocking its physiological functions, affecting the apelinergic system, and inhibiting the cleavage of its peptides. The appropriate concentration of peptides in the apelinergic system influences the maintenance of homeostasis and protects against cardiovascular diseases. In our research, we determined the level of selected parameters of the apelinergic system—apelin (AP), elabela (ELA), and the apelin receptor (APJ)—in repeat blood donors. Methods: We analyzed 120 serum samples obtained from 30 repeat donors (study group) within four time periods after a SARS-CoV-2 infection: <60 days, 61–90 days, 91–120 days, and >120 days. We compared the results from the study groups with those of the control group, which consisted of 30 serum samples collected from donors donating blood in the years 2018–2019. Results: We observed that the AP, ELA, and APJ concentrations in the control group are higher than in any period in the study group. In the study group, the concentrations of AP and ELA increased in subsequent study periods. AP and ELA concentrations were lower shortly after SARS-CoV-2 transfection and then slowly increased in subsequent periods. APJ concentrations, on the other hand, were lowest at 61–90 days after the infection, but the decrease, relative to their level in healthy subjects, was significant in every period studied. Conclusions: The results suggest that infection with SARS-CoV-2 causes changes in the parameters of the apelinergic system, both after a short period of time has passed since the onset of the SARS-CoV-2 infection, and even up to 4 months after the infection.